2023
DOI: 10.1039/d2bm01915a
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione peroxidase-like nanozymes: mechanism, classification, and bioapplication

Abstract: The field of nanozymes is developing rapidly. In particular, glutathione peroxidase (GPx)-like nanozymes, which catalytically reduce H2O2/organic hydroperoxides to H2O/alcohols, have generated considerable attention. GPx-like nanozymes are powerful antioxidant enzymes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 127 publications
0
9
0
Order By: Relevance
“…31 Subsequently, it was observed that V 2 O 5 nanowires also catalyze the glutathione peroxidase-dependent conversion of GSH (reduced glutathione) to glutathione disulfide. 32 Further research has also evidenced that graphene oxide (GO) and single-walled carbon nanotubes (SWCNs) are also capable of imitating HRP. 33 These carbon-based nanomaterials are shown to catalyze the oxidation reaction of TMB and H 2 O 2 to yield a blue-colored product at pH 4, which resembles the working condition of the HRP enzyme.…”
Section: ■ Nanozymes: Structure and Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Subsequently, it was observed that V 2 O 5 nanowires also catalyze the glutathione peroxidase-dependent conversion of GSH (reduced glutathione) to glutathione disulfide. 32 Further research has also evidenced that graphene oxide (GO) and single-walled carbon nanotubes (SWCNs) are also capable of imitating HRP. 33 These carbon-based nanomaterials are shown to catalyze the oxidation reaction of TMB and H 2 O 2 to yield a blue-colored product at pH 4, which resembles the working condition of the HRP enzyme.…”
Section: ■ Nanozymes: Structure and Functionsmentioning
confidence: 99%
“…In the presence of H 2 O 2 , V 2 O 5 (vanadium pentoxide) nanowires can mimic V-HPOs and convert bromide into water and HOBr . Subsequently, it was observed that V 2 O 5 nanowires also catalyze the glutathione peroxidase-dependent conversion of GSH (reduced glutathione) to glutathione disulfide …”
Section: Mode Of Actionmentioning
confidence: 99%
“…63,64 Selenium was found to be an important component in GPx; therefore, researchers initially explored GPx mimetic enzymes pertaining to selenium-based compounds. 64 It catalyzes the change of GSH (reduced glutathione) to GSSG (oxidized glutathione). Li et al 65 reported an ultrasmall bimetallic oxide nanozyme (CuFe 2 O 4 −PEG) that exhibited GPx-like activity in addition to POD-and CAT-like activities.…”
Section: Peroxide-like Activitymentioning
confidence: 99%
“…Glutathione peroxidase (GPx) is an antioxidant enzyme responsible for maintaining cellular redox homeostasis. , Selenium was found to be an important component in GPx; therefore, researchers initially explored GPx mimetic enzymes pertaining to selenium-based compounds . It catalyzes the change of GSH (reduced glutathione) to GSSG (oxidized glutathione).…”
Section: Nanozymementioning
confidence: 99%
See 1 more Smart Citation